ANALISIS UI DAN UX TERHADAP WEBSITE PT. BROTHERSINDO SAUDARA SEJATI DENGAN METODE HEURISTIC EVALUATION - Noviani, Sherli; Serli, Rosi Kusuma; Palasara, Nicodias (CONTEN : Computer and Network Technology, 2024)
All kinds of community activities are inseparable from the help of technology. The development of the business world in Indonesia is experiencing tough competition. Consumer satisfaction is the degree of conformity between the desired product and/or service and the reality received. The level of suitability is the result of an assessment carried out by the customer based on his knowledge and experience. Information system applications technically can be defined as a set of components that are interconnected to support decision making and drive the company. As the operation goes on, it is certainly possible for money problems to arise including the user interface and user experience. To measure user satisfaction and comfort with the Brothersindo Website, you can do usability testing using the heuristic evaluation method. The heuristic evaluation method is a method used to find errors in interface design based on 10 heuristic evaluation principles. Keywords: heuristic evaluation, sales website, user interface dan user experience